Abnormal psychology : - Alloy, Lauren B. (McGraw-Hill, 2004)
Part one: Introduction to abnormal psychology. Abnormal psychology: historical perspectives -- Diagnosis and assessment -- Research methods in abnormal psychology -- Part two: Theoretical perspectives. The behavioral, cognitive, and sociocultural perspectives -- The psychodynamic, humanistic-existential, and interpersonal perspectives -- The neuroscience perspective -- Part three: Emotional and behavioral disorders. Anxiety disorders -- Dissociative and somatoform disorders -- Stress and physical disorders -- Mood disorders -- Personality disorders -- The Nature of substance dependence and abuse -- Sexual dysfunctions, paraphilias, and gender identity disorders -- Part four: Psychotic and neuropsychological disorders. Schizophrenia and delusional disorder -- Neuropsychological disorders -- Part five: Developmental disorders. Disorders of childhood and adolescence -- Mental retardation and autism -- Part six: Legal and ethical issues in abnormal psychology -- Legal and ethical issues in abnormal psychology.